Expression Versus Distraction: An Investigation of Contrasting Emotion Regulation Strategies When Drawing, Writing, Talking, and Thinking. (July 2018) - James, Ciara; Drake, Jennifer E.; Winner, Ellen
While the benefit of distraction over expression as an emotion regulation strategy has been shown, it is not clear whether this benefit generalizes across a range of activities. To find out, we compared distraction versus expression in drawing, writing, talking, and thinking to oneself. We induced a negative mood in 160 participants by asking them to visualize an upsetting experience. Participants were randomly assigned to an emotion regulation strategy (express or distract) and an activity (draw, write, talk, or think). Positive and negative affect was measured before and after the mood induction and after the activity. Distraction boosted positive affect more than did expression for the draw and think activities, but distraction lowered negative affect more than did expression for all four activities. We conclude that distraction is a more effective emotion regulation strategy than expression in improving mood especially for activities that involve drawing and thinking.